The Undoing Effect of Positive Emotions - Fredrickson, Barbara L. (2000)
Positive emotions are hypothesized to undo the cardiovascular aftereffects of negative emotions. Study 1 tests this undoing effect. Participants (n = 170) experiencing anxiety-induced cardiovascular reactivity viewed a film that elicited (a) contentment, (b) amusement, (c) neutrality, or (d) sadness. Contentment-eliciting and amusing films produced faster cardiovascular recovery than neutral or sad films did. Participants in Study 2 (n = 185) viewed these same films following a neutral state. Results disconfirm the alternative explanation that the undoing effect reflects a simple replacement process. Findings are contextualized by Fredrickson’s broaden-and-build theory of positive emotions (B. L. Fredrickson, 1998).